2018
DOI: 10.1039/c8qm00372f
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive and selective two-photon fluorescent probe for real-time sensing of cytochrome P450 1A1 in living systems

Abstract: We designed and developed a highly sensitive and selective two-photon fluorescent probe for real-time tracking CYP1A1 activity in cancer tissues and zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“… Substrate Metabolite K m or S 50 (μmol/L) V max or K cat λ ex (nm)/ λ em (nm) Ref. CYP1A1 CYP1A1-F1 0.84 18.99 a 450/562 32 CYP1A1-F2 0.29 5.54 a 470/525 35 CYP1A1-F3 11.99 17.44 a 450/564 153 CYP1A1-F4 N.A. N.A.…”
Section: Optical Substrates For Phase I Drug-metabolizing Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“… Substrate Metabolite K m or S 50 (μmol/L) V max or K cat λ ex (nm)/ λ em (nm) Ref. CYP1A1 CYP1A1-F1 0.84 18.99 a 450/562 32 CYP1A1-F2 0.29 5.54 a 470/525 35 CYP1A1-F3 11.99 17.44 a 450/564 153 CYP1A1-F4 N.A. N.A.…”
Section: Optical Substrates For Phase I Drug-metabolizing Enzymesmentioning
confidence: 99%
“…Inspired by the development of CYP1A1-F1, Ning et al. 35 have reported a new two-photon fluorescent substrate (CYP1A1-F2) for CYP1A1, which was designed based on the substrate preferences of CYP1A1 and the principle of intramolecular charge transfer (ICT). Recently, a resorufin-based substrate (CYP1A1-F8) for highly selective and sensitive sensing CYP1A1 activities has been developed by Jin et al.…”
Section: Optical Substrates For Phase I Drug-metabolizing Enzymesmentioning
confidence: 99%
“…7H-Benzo[de]benzo [4,5]imidazo[2,1-a]isoquinolin-7-one (BN) was selected as a suitable fluorophore due to its known CYP binding ability [19] and prominent photo-physicochemical properties such as two-photon absorption and high fluorescence quantum yield. [20] On dissection of the key binding domain of the BN with CYP3A, it was found that the benzene ring of the benzimidazole (Head group, marked as b in light-green in Scheme 1A) plays an important role.…”
Section: Mechanism-based Inactivation (Mbi) Of Enzymes Convertsmentioning
confidence: 99%
“…7H-Benzo[de]benzo [4,5]imidazo[2,1-a]isoquinolin-7-one (BN) was selected as a suitable fluorophore due to its known CYP binding ability [19] and prominent photo-physicochemical properties such as two-photon absorption and high fluorescence quantum yield. [20] On dissection of the key binding domain of the BN with CYP3A, it was found that the benzene ring of the benzimidazole (Head group, marked as b in light-green in Scheme 1A) plays an important role.…”
Section: Mechanism-based Inactivation (Mbi) Of Enzymes Convertsmentioning
confidence: 99%